Swedish election study 1976 - Petersson, Olof; Statistics Sweden (University of Gothenburg, 1982)
This study is part of the collection of Swedish election studies fielded continuously since 1956. The 1976 study was the first election study to cover the nuclear power issue, an issue which for many years became one of the central political issues in Sweden. This study also includes a large number of questions on how different groups in society are treated by different political parties, it also includes a number of questions on different groups´ and organizations´ influence in society. This study introduces a number of questions, asked in all or nearly all of the election studies since then, about the respondent´s opinion on different issues such as day-care centers, pornography, socialization, defence expenditures, private enterprise, and taxes.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

Valundersökningen 1976 är den sjunde riksomfattande studien i serien undersökningar kring partival, valdeltagande och politisk opinionsbildning inom den svenska valmanskåren i samband med ett riksdagsval. Denna undersökninga genomfördes i samarbete mellan statsvetenskapliga institutionen vid Uppsala universitet och statistiska centralbyrån.

1976 års undersökning är den första valundersökning som täcker kärnkraftsfrågan, ett ämne som under många år var en av de centrala politiska frågorna i Sverige. Undersökningen innehåller ett stort antal frågor om hur olika samhällsgrupper behandlas av de olika politiska partierna. Den innehåller även ett antal frågor om olika gruppers och organisationers inflytande i samhället. I samband med 1976 års undersökning introducerades ett antal frågor som sedan ställts i samtliga, eller nästan samtliga, valundersökningar som genomförts därefter. Dessa frågor behandlar respondentens inställning till en rad ämnen såsom, daghem, pornografi, förstatligande, militärutgifter, företagsamhet och skatter.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Svensk valundersökning 1976
VU76
Keywords: elections; val; mass media; massmedia; occupations; yrken; participation; deltagande; politics; politik; public sector; offentlig sektor; social mobility; social rörlighet; ethics; etik; international relations; internationella relationer; employment; anställning; energy; energi; voting; röstning; political interest; politiskt intresse; energy policy; energipolitik; taxation; beskattning; political allegiance; politisk anhängare; political participation; politiskt deltagande; internal politics; inrikespolitik; political parties; politiska partier; trade unions; fackföreningar; organizations; organisationer; political attitudes; politiska åsikter; lobbying; politisk påverkan; CORS; CORS; Media; Media; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap